On Blockchain Performance Enhancement: A Systematic Map of Strategies Used - Kigombola, Anthony; Mbise, Mercy; Mafole, Prosper (Tanzania Journal of Engineering and Technology, 2023)
Blockchain technology is one among the recent innovations in the computing industry. Blockchains have gathered a widespread interest in the industry mainly due to their security promise. Despite the anticipated benefits of Blockchains, there are several limitations which make the technology less suitable in large scale applications such as banking, one being low throughput. Several initiatives to improve the throughput of Blockchains are being tried out both in the academia and the business worlds but no systematic classification of the initiatives and the strategies used has been done. This study explores Blockchain performance improvement initiatives and classify the initiatives by the improvement strategy used. This study has found that, out of 365 articles on the area of Blockchain performance, 300 were solution proposals aimed at improving the performance of Blockchains. The most used strategies in these proposals were alternative to PoW, sharding and multi-chain architecture. Keywords: Blockchain, performance enhancement, throughput